2018
DOI: 10.1371/journal.pone.0205339
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the age-specificity of measles transmissions during 2009-2016 in Southern China

Abstract: BackgroundDespite several immunization efforts, China saw a resurgence of measles in 2012. Monitoring of transmissions of individuals from different age groups could offer information that would be valuable for planning adequate disease control strategies. We compared the age-specific effective reproductive numbers (R) of measles during 2009–2016 in Guangdong, China.MethodsWe estimated the age-specific R values for 7 age groups: 0–8 months, 9–18 months, 19 months to 6 years, 7–15 years, 16–25 years, 26–45 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…One of the changes was that children aged <8 months, who were expected to be protected by maternal antibodies before receiving the first dose of MV (MV1), became the age group with the greatest risk of infection in recent years. The age-specific incidence of measles among young infants was higher compared to the other age groups [7,8]. Some local serological studies conducted among young infants found that early waning of maternal antibodies against measles might be the primary cause [9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…One of the changes was that children aged <8 months, who were expected to be protected by maternal antibodies before receiving the first dose of MV (MV1), became the age group with the greatest risk of infection in recent years. The age-specific incidence of measles among young infants was higher compared to the other age groups [7,8]. Some local serological studies conducted among young infants found that early waning of maternal antibodies against measles might be the primary cause [9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In Mongolia from 2015 to 2016, the measles season among children age 0–11 months occurred from July to October [16]. From 2012 to 2016, the number of confirmed measles patients under age 18 months was highest between May and August in Guangdong province [17]. In our study, 71.32% of patients were under age 18 months, which could be a factor affecting the measles season.…”
Section: Discussionmentioning
confidence: 63%
“…Relatively high proportions of adult patients were also observed after the SIAs were introduced in other studies [20,21]. The decreasing incidence in the overall population, declining birth rate, and increasing vaccination coverage among infants and children compared to the low coverage rate in the 1980s and earlier [37,38] all contributed to the increasing mean age of infection and build-up of susceptible individuals among adults [39]. In China, infections among adults were mainly due to susceptibility caused by missed vaccinations and decreased opportunities for acquiring immunity through natural infection [38,40].…”
Section: Discussionmentioning
confidence: 64%